Question

\[ f(x) = 3x + 4 \quad g(x) = 2x - 3 \] \[ \text{Find: } f \circ g(x) \]

Ask by Estrada Ramirez. in the United States
Jan 30,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( f \circ g(x) = 6x - 5 \)

Solution

To find the composition \( f \circ g(x) \), we substitute \( g(x) \) into \( f(x) \). Given: \[ f(x) = 3x + 4 \quad \text{and} \quad g(x) = 2x - 3 \] Compute \( f(g(x)) \): \[ f(g(x)) = f(2x - 3) = 3(2x - 3) + 4 \] \[ = 6x - 9 + 4 \] \[ = 6x - 5 \] So, the composition \( f \circ g(x) \) is: \[ f \circ g(x) = 6x - 5 \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To find \( f \circ g(x) \), which means \( f(g(x)) \), we need to substitute \( g(x) \) into \( f(x) \). First, let's calculate \( g(x) \): \[ g(x) = 2x - 3 \] Now we substitute \( g(x) \) into \( f(x) \): \[ f(g(x)) = f(2x - 3) \] Now, using the function \( f(x) = 3x + 4 \): \[ f(2x - 3) = 3(2x - 3) + 4 \] Distributing the 3: \[ = 6x - 9 + 4 \] Combining the constants: \[ = 6x - 5 \] Thus, the result of \( f \circ g(x) \) is: \[ f \circ g(x) = 6x - 5 \]

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy